Untying the Gordian knot of pericardial diseases: A pragmatic approach - George Lazaros; Massimo Imazio; Antonio Brucato; Dimitrios Tousoulis (Hellenic Journal of Cardiology, 2016)
Pericardial disorders constitute a relatively common cause of heart disease. Although acute pericarditis, especially the idiopathic forms that are the most prevalent, is considered a benign disease overall, its short- and long-term complications, namely, recurrent pericarditis, cardiac tamponade and constrictive pericarditis, constitute a matter of concern in the medical community. In recent years, several clinical trials contributed to redefining our traditional approach to pericardial diseases. In this review, we provide the most recent evidence concerning diagnosis, treatment modalities and short- and long-term prognosis of the most common pericardial disorders.